Development of Chicken Sausages: Value Addition to Spent Hen Meat - Roberts, T. P. Pradeepa; Kusuma, D. L.; Sucharitha, K. V.; Bharathi, R. (International Journal of Livestock Research, 2019)
India is the most popular country for the production of poultry eggs which lead to the problem with the disposal off spent hens. Utilization of such spent hen meat is a big challenge to modify into potential palatable value-added products. The present study had made an attempt to develop chicken sausages using spent hen meat. Two varieties of chicken sausages were developed viz., one without ginger garlic paste and the other with incorporation of ginger garlic paste at three percent level and stored at refrigerated temperatures (-18±10 c) for a period of 60 days at 15 days intervals. The sensory evaluation results on cooked samples clearly demonstrated highly acceptable scores in the fresh samples and slightly lower scores on storage. The experimental samples scored relatively better than control sample indicating the positive effectiveness with the incorporation of ginger garlic paste on enhancing the palatability as well as shelf life.